Microautophagy Mediates Vacuolar Delivery of Storage Proteins in Maize Aleurone Cells - Ding, Xinxin; Zhang, Xiaoguo; Paez-Valencia, Julio; McLoughlin, Fionn; Reyes, Francisca C.; Morohashi, Kengo; Grotewold, Erich; Vierstra, Richard D.; Otegui, Marisa S. (Frontiers in Plant Science, 2022)
The molecular machinery orchestrating microautophagy, whereby eukaryotic cells sequester autophagic cargo by direct invagination of the vacuolar/lysosomal membrane, is still largely unknown, especially in plants. Here, we demonstrate microautophagy of storage proteins in the maize aleurone cells of the endosperm and analyzed proteins with potential regulatory roles in this process. Within the cereal endosperm, starchy endosperm cells accumulate storage proteins (mostly prolamins) and starch whereas the peripheral aleurone cells store oils, storage proteins, and specialized metabolites. Although both cell types synthesize prolamins, they employ different pathways for their subcellular trafficking. Starchy endosperm cells accumulate prolamins in protein bodies within the endoplasmic reticulum (ER), whereas aleurone cells deliver prolamins to vacuoles via an autophagic mechanism, which we show is by direct association of ER prolamin bodies with the tonoplast followed by engulfment via microautophagy. To identify candidate proteins regulating this process, we performed RNA-seq transcriptomic comparisons of aleurone and starchy endosperm tissues during seed development and proteomic analysis on tonoplast-enriched fractions of aleurone cells. From these datasets, we identified 10 candidate proteins with potential roles in membrane modification and/or microautophagy, including phospholipase-Dα5 and a possible EUL-like lectin. We found that both proteins increased the frequency of tonoplast invaginations when overexpressed in Arabidopsis leaf protoplasts and are highly enriched at the tonoplast surface surrounding ER protein bodies in maize aleurone cells, thus supporting their potential connections to microautophagy. Collectively, this candidate list now provides useful tools to study microautophagy in plants.